On-chip AMBA Bus Based Efficient Bridge between High Performance and Low Peripheral Devices - Anurag Shrivastava; Sudhir Kumar Sharma (International Journal of Reconfigurable and Embedded Systems (IJRES), 2017)
Today’s scenario of SOC deals with integrity and sharing of information or data with various level of communication. AMBA bus protocol has been proposed by ARM community to justify the uneven demand of integrity .In this paper functional description and implementation of high peripheral devices supporting protocol AXI2.0 and its interface between low peripheral devices has been proposed. The connection named as bridge take care of the protocol mismatch and operates on data transfer for uneven speed demand. Asynchronous   FIFO has been considered to avoid the complex handshaking mechanism. The design has been implemented within VHDL and implemented on Xilinx Virtex 4.